2020
DOI: 10.1098/rstb.2020.0075
|View full text |Cite
|
Sign up to set email alerts
|

Sperm and alternative reproductive tactics: a review of existing theory and empirical data

Abstract: Males that exhibit alternative reproductive tactics (ARTs) often differ in the risk of sperm competition and the energetic trade-offs they experience. The resulting patterns of selection could lead to between-tactic differences in ejaculate traits. Despite extensive research on male ARTs, there is no comprehensive review of whether and what differences in sperm traits exist between male ARTs. We review existing theory on ejaculate evolution relevant to ARTs and then conduct a comprehensive vote-counting review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 91 publications
5
49
0
Order By: Relevance
“…This intraspecific variation has been mainly attributed to differences among populations, male genetic background, developmental environment or mating tactics 4 8 . The latter explains, for example, the large differences in sperm quality and number among males adopting alternative mating tactics such as territorial and sneaker males, where different sperm traits are favoured under different mating circumstances 9 , 10 . There is also evidence of significant variation across ejaculates of the same males, so that variation exists both in the number of sperm produced and in their quality even when produced from the same male.…”
Section: Introductionmentioning
confidence: 99%
“…This intraspecific variation has been mainly attributed to differences among populations, male genetic background, developmental environment or mating tactics 4 8 . The latter explains, for example, the large differences in sperm quality and number among males adopting alternative mating tactics such as territorial and sneaker males, where different sperm traits are favoured under different mating circumstances 9 , 10 . There is also evidence of significant variation across ejaculates of the same males, so that variation exists both in the number of sperm produced and in their quality even when produced from the same male.…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, Gage showed how male insects exposed to rivals during copulation increased the number of sperm they transferred to females [30,31] and studies across a diverse array of taxa have since reported similar patterns, indicating that in general males will allocate their sperm strategically in response to the risk of sperm competition [63]. In their contribution to this themed issue, Kustra and Alonzo [64] review the literature on alternative reproductive tactics (ARTs), finding that a consistent pattern across those species that adopt ARTs is that males in the sneaking role have larger testes, and so produce more sperm, than those in the guarding role.…”
Section: Rapid Growthmentioning
confidence: 99%
“…Consequently, small males often exhibit alternative mating tactics, such as sneaking or female mimicking, to approach females and compensate for their lower chances of winning physical contests against larger competitors, thereby maximizing their reproductive success [ 1 , 2 ]. In accordance with these behavioural tactics, small males also invest more reproductive resources on ejaculate traits than larger males, primarily in quantity (relative or absolute sperm number) but also occasionally in quality (e.g., sperm swimming performance) [ 3 ]. Because the individual benefits of these behavioural and ejaculate traits on reproductive success depend on social status/agonistic ranks that can change during growth or aging [ 4 ], sperm traits should ideally be developed or switched into fitness optima according to their prospects.…”
Section: Introductionmentioning
confidence: 99%